2008
DOI: 10.1080/03115510801944970
|View full text |Cite
|
Sign up to set email alerts
|

A late Changhsingian (latest Permian) radiolarian fauna from Chaohu, Anhui and a comparison with its contemporary faunas of South China

Abstract: A well-preserved late Changhsingian radiolarian fauna (15 species attributed to 12 genera) is recorded from the upper part of the Talung This fauna is more diverse than the fauna from the Meishan section in Zhejiang Province but is less diverse than the fauna of the Dongpan section in Guangxi Province, South China. The new fauna incorporates a higher percentage of Latentifistularia forms than the fauna from the Meishan section, but incorporates a lower percentage of Latentifistularia and Albaillellaria forms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…According to Kozur (1993) (see also Feng & Ye 2000;He et al 2008), if a radiolarian assemblage is dominated by albaillellarians or latentifistularians it would suggest outer shelf to abyssal water depths in excess of 150 m. In South China, abundant albaillellarians and latentifistularians have been discovered at the Hushan (He et al 2011), Majiashan , Rencunping, Shaiwa (Wang & Shang 2001), Dongpan (Feng et al 2007), Paibi (Wu & Feng 2008), Liuqiao (Wu & Feng 2008) and Duanshan sections (Feng Qinglai pers. comm.).…”
Section: Geographical and Geological Settingsmentioning
confidence: 96%
“…According to Kozur (1993) (see also Feng & Ye 2000;He et al 2008), if a radiolarian assemblage is dominated by albaillellarians or latentifistularians it would suggest outer shelf to abyssal water depths in excess of 150 m. In South China, abundant albaillellarians and latentifistularians have been discovered at the Hushan (He et al 2011), Majiashan , Rencunping, Shaiwa (Wang & Shang 2001), Dongpan (Feng et al 2007), Paibi (Wu & Feng 2008), Liuqiao (Wu & Feng 2008) and Duanshan sections (Feng Qinglai pers. comm.).…”
Section: Geographical and Geological Settingsmentioning
confidence: 96%
“…Previous work has shown that the distribution of radiolarian taxa is sensitive to the changes of the water depth (e.g., Feng, 1992b; He et al, 2008; Kozur, 1993; Xiao et al, 2017). Feng (1992b) generally stated that albaillellarians were mainly distributed in deep water, and assemblages dominated by spumellarians mostly occurred in shallow water.…”
Section: Discussionmentioning
confidence: 99%
“…Kozur (1993) studied the Late Permian radiolarians of the Sosio Valley in Italy and West Texas in the United States, and found (i) a shallow‐water radiolarian association down to 50 m water depth consisted almost exclusively of spumellarians (of the family Copicyntridae); (ii) the interval of 50–500 m water depth was dominated by entactinarians, accompanied in the shallower waters by spumellarians (of the family Copicyntridae), and below 200 m depth by rare albaillellarians; and (iii) in water depths below 500 m, albaillellaians were dominant, accompanied by variable amounts of entactinarians and latentifistularians. He et al (2008) studied the Changhsingian radiolarians of the Chaohu, Meishan, and Dongpan sections in South China, representing depositional environments of different water depths. They recognized that (i) shallow water settings (<60 m) (Meishan section) were dominated by entactinarians or spumellarians, with <30% of the total being latentifistularians (or together with albaillellarians); (ii) in water depths between 60–150 m (Chaohu section), faunas were with 30%–40% latentifistularians (or together with albaillellarians); (iii) when water depths >200 m (Dongpan section), latentifistularians plus albaillellarians became common (>40%).…”
Section: Discussionmentioning
confidence: 99%
“…In radiolarian assemblages, the relative abundance of the Albaillellaria and Latentifistularia (orders), can be used to determine the relative water depths (a higher percentage of Albaillellaria plus Latentifistularia forms compared with all other radiolarian orders implies deeper waters; see He et al 2007bHe et al , 2008. In the northern part of the deepwater South China Basin (such as at the Hushan, Majiashan and Recunping sections), the ratio of Albaillellaria plus Latentifistularia forms to all radiolarian orders varies between 29 and 50%, whereas this ratio is 42-59% in the southern part of the basin (such as at Shaiwa and Dongpan sections) [for data from Majiashan see He et al (2008); for data from Shaiwa see Wang & Shang (2001); for data from Dongpan see Feng et al (2007); for data from Hushan see He et al (2011); the data for Rencunping is unpublished]. The difference in the ratio suggests that it was deeper in the south (a bathyal zone) than in the north (an outer shelf setting).…”
Section: Palaeogeographical Distribution Of Brachiopodsmentioning
confidence: 99%